Evaluación técnica de las propiedades mecánicas de un liner ranurado mediante pruebas estandarizadas para la industria petrolera (2018)
In the present project of degree they evaluated the mechanical properties for a slotted liner through the following tests: collapse, burst, torsion, compression and tension. These tests were carried out only to two types of slotted liners, since they are the most sold liner types by the Company de Petroleo y Gas y Energías Renovables SAS, one of these is 4 ½ "in diameter with a nominal weight of 11.6 lbs / ft - grade N80 - range 3 - BTC connection - slot thickness 0.04 "- groove density 104 slots / foot and the other 7" in diameter with a nominal weight of 23 lbs / ft - grade N80 - range 3 - BTC connection - slot thickness 0.012 "- slot density 320 slots / foot; these tests were carried out only in the laboratory. The evaluation of the mechanical properties of the slotted liner were carried out in the laboratory of the Company Petroleo y Gas y Energías Renovables SAS, where the above-mentioned tests were run, achieving a comparison between the mechanical properties of a conventional liner and a Slotted liner.